Análise estereológica e funcional do testículo de rãs-touro (Lithobates catesbeianus) sexualmente maduras, com ênfase na cinética espermatogonial, proliferação e número de células de sertoli por cisto espermatogênico - Luiz Henrique de Castro Assis (2011)
Spermatogenesis is a complex and cyclic process that results in the daily production of millions of sperm. Although there are particularities among different species, this process seems to be very well conserved in the different vertebrate classes, and the morphofunctional interactions between somatic cells and germ cells (GC) are crucial to its success. Due to its substantial economic importance, the bullfrog (Lithobates catesbeianus) is an amphibian species that was introduced in Brazil around 1930. Although this species is a useful model in biological research, including studies related to the reproductive biology, the knowledge of its testicular structure and function is still scarce. In this regard, the main objectives of the present study were to perform a careful histological and morphofunctional analysis of sexually mature bullfrogtestis, with emphasis on the spermatogonial kinetics as well as in the proliferation rate of testis somatic elements [Sertoli cell (SC); Leydig cell (LC), and peritubular myoid cell (PMC)] and the number of GC and SC per spermatogenic cyst. For this purpose, sixteen bullfrogs were used and, aiming to estimate the proliferation rates, eight of them received a single intracelomic injection of tritiated thymidine (1Ci/g/BW) and theirtestes were collected 2 to 3 hours after injection. All animals were anesthetized and their testis were removed and transversely and longitudinally sectioned, in order to obtain fragments that represented six different testis regions previously defined. These fragments were then fixed by immersion in 4% glutaraldehyde, routinely embedded inglycol-methacrylate and processed for histomorphometric and radioautography analysis. No evident differences were observed for the arrangement of the seminiferous tubules as well as for the spermatogenic activity and the volume densities (%) of tubularand intertubular compartments in the six different regions investigated. These results indicate that the components of the testicular parenchyma in the bull-frog exhibit a homogeneous distribution. Also, the results showed that all bull-frogs investigated presented full spermatogenic activity. Based on the morphological characterization of the different spermatogenic cells and on the germ cells counts per cyst, eightspermatogonial generations were found for this species - one of type A and seven of type B spermatogonia. As observed for other lower vertebrates species investigated, the GC nuclear, cytoplasmic and cellular volumes decreased strikingly from type A spermatogonia to spermatids. However, a small but significant increase in theleptotene/zygotene primary spermatocytes volume was observed. The SC nuclear diameter and volume were relatively stable in the spermatogonial and meiotic cysts (up to diplotene), increasing markedly thereafter until late spermatid. As expected, the number of GC per cyst increased dramatically from type A spermatogonia to early spermatids. Moreover, the number of SC increased gradually from type A to late type Bspermatogonial cysts, with further increase in the late meiotic phase (diplotene) of spermatogenesis, tending to stabilize thereafter. Apparently, the spermatogenic cysts frequencies reflected the duration of each of the three phases of spermatogenesis (previously estimated in our laboratory) where espermatogonial phase was much longerthan the two other phases. Although at a small magnitude and based on the GC counts, apoptosis seems to occur in all the three phases of spermatogenesis, resulting in the production of 50% of the spermatids theoretically expected. Similar to the findings related to the other parameters, the somatic cells proliferation ratios showed nosignificant differences among the six different regions evaluated. However, in relation to the proliferation rates of somatic cells associated or close to the different types of spermatogenic cysts, SC proliferation was preferentially associated with type B spermatogonia, suggesting an adequacy of the SC number to support the highly increase of GC numbers that occurs in this particular spermatogenic cysts. On the other hand, no clear trend was observed for the LC and PMC. Finally, besides characterizing more accurately the testis structure and function in bullfrogs, allowing comparison of these data with those obtained for other vertebrates species, we expect that the results found in the present study may be very useful in future research addressing the Lithobates catesbeianus as an experimental model.